Obesity in Type 1 Diabetes: Pathophysiology, Clinical Impact, and Mechanisms - Corbin, Karen D; Driscoll, Kimberly A; Pratley, Richard E; Smith, Steven R; Maahs, David M; Mayer-Davis, Elizabeth J (Endocrine reviews, 2018)
There has been an alarming increase in the prevalence of obesity in people with type 1 diabetes in recent years. Although obesity has long been recognized as a major risk factor for the development of type 2 diabetes and a catalyst for complications, much less is known about the role of obesity in the initiation and pathogenesis of type 1 diabetes. Emerging evidence suggests that obesity contributes to insulin resistance, dyslipidemia, and cardiometabolic complications in type 1 diabetes. Unique therapeutic strategies may be required to address these comorbidities within the context of intensive insulin therapy, which promotes weight gain. There is an urgent need for clinical guidelines for the prevention and management of obesity in type 1 diabetes. The development of these recommendations will require a transdisciplinary research strategy addressing metabolism, molecular mechanisms, lifestyle, neuropsychology, and novel therapeutics. In this review, the prevalence, clinical impact, energy balance physiology, and potential mechanisms of obesity in type 1 diabetes are described, with a special focus on the substantial gaps in knowledge in this field. Our goal is to provide a framework for the evidence base needed to develop type 1 diabetes-specific weight management recommendations that account for the competing outcomes of glycemic control and weight management.